Ethnobotanical Survey of Selected Medicinal Plants Used By the Ogiek Communities in Kenya against Microbial Infections - Amuka, Omari; Machocho, Alex k.; Mbugua, Paul K; Okemo, Paul O. (Ethnobotany Research and Applications, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –> The role played by traditional medicine based on the use of medicinal plants for health purposes is significant both in growing and developed economies. Although the use of medicinal plants is already considerably documented across the globe, their increased use has only been noted in the recent past. In the African context, however, the dosage of such plants together with their pharmacological observations is yet to be well documented. In this paper, an attempt is made at documenting such knowledge with respect to traditional medicine among the Ogiek for future generations and to serve as a repository for further scientific studies on traditional medicine. The study was carried out involving the Ogiek community who live in the Mau forests in the central Rift Valley of Kenya where they still depend largely on hunting and gathering. A total of 20 traditional healers aged between 50 and 70 years were interviewed by use of a questionnaire. It was evident from the 32 plant families collected that the majority are used in treating malaria (21.88%), pneumonia (21.88%), stomachache (21.88%), and tonic related diseases (21.88%). Other remedies used fewer plant families. It is therefore recommended that follow up studies pertaining to these plants be carried out for validation of their efficacy by in vitro and in vivo studies. It is also recommended that further studies on hygienic administration of these drugs be carried out. Conservation of the endangered plant species involving conventional methods should be encouraged. There should be clear policies regarding traditional medical practices in Kenya and elsewhere in East Africa.